Nutritional composition of industrialized, homemade and vegan foods for dogs and cats: A systematic review (Research, Society and Development, 2023)
Industrialized or homemade foods for dogs and cats are widely studied in terms of ingredients and how they are fed to pets. Over the last few decades, research has been seeking ingredients that promote not only good nutrition, but that promote greater longevity and quality of life for animals, whether using new sources of animal or vegetable protein, dietary fiber, carbohydrates, among other ingredients that become essential to the health and well-being of pets. The objective of this research was to analyze, through a systematic review of the literature, the new ingredients that are part of the composition of foods offered to small animals. The study was conducted following the recommendations of the PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) with identification of articles in the Web of Science, PubMed, Science Direct and Scopus databases. 13,131 articles were found and, after applying the methodological criteria, 42 articles were still fully evaluated. It can be seen from this research that several ingredients such as new sources of proteins, carbohydrates and fiber, in addition to the industrialization process and research on the quality and digestibility of these new ingredients, proved to be essential and important to contribute to nutrition and better use of ingredients. in processed food.